Local Neuronal Synchronization in Frequent Nightmare Recallers and Healthy Controls: A Resting-State Functional Magnetic Resonance Imaging Study - Marquis, Louis-Philippe; Julien, Sarah-Hélène; Daneault, Véronique; Blanchette-Carrière, Cloé; Paquette, Tyna; Carr, Michelle; Soucy, Jean-Paul; Montplaisir, Jacques; Nielsen, Tore (Frontiers in Neuroscience, 2021)
Nightmares are defined as highly dysphoric dream that are well-remembered upon awakening. Frequent nightmares have been associated with psychopathology and emotional dysregulation, yet their neural mechanisms remain largely unknown. A neurocognitive model posits that nightmares reflect a dysfunction in a limbic-prefrontal circuit comprising medial prefrontal and anterior cingulate cortices, hippocampus, and amygdala. However, there is a paucity of studies that used brain imaging do directly test the neural correlates of nightmares. One such study compared the regional homogeneity of resting-state functional magnetic resonance imaging blood-oxygen level-dependent signal between frequent nightmares recallers and controls. The main results were increased regional homogeneity in the left anterior cingulate cortex and right inferior parietal lobule for the nightmare recallers compared to the control group. Regional homogeneity of these two regions was also associated with the Physical Effect subscale of the Nightmare Experience Questionnaire. We aim to replicate and expand upon this past studydocument the ReHo correlates of frequent nightmares using several nightmare severity measures . In the present study, we acquired resting-state functional magnetic resonance imaging data from 18 frequent nightmare recallers aged 18-35 (3 M, 15F) and 18 age and sex-matched controls, as well as retrospective and prospective disturbed dreaming frequency estimates and scores on the Nightmare Distress Questionnaire. Overall, we failed to replicate past research, but conceptually replicated part of the results. While there were inconsistent results for our different analyses (group comparisons, correlational analyses for frequency estimates/Nightmare Distress scores), our results suggest that nightmares are associated with altered regional homogeneity in various frontal (medial prefrontal, anterior cingulate corticesinferior frontal), parietal, temporal and occipital regions, as well as some subcortical regions (putamen, thalamus, hippocampus). We also found a positive correlation between retrospective disturbed dreaming frequency estimates and ReHo values in the hippocampus. These findings are more mostly in line with a recent SPECT study from our laboratory. Our results point to the possibility that a variety of regions, including but not limited to the limbic-prefrontal circuit of the neurocognive model, contribute to nightmare formation.